Evaluation of Rhamnetin as an Inhibitor of the Pharmacological Effect of Secretory Phospholipase A2 - Belchor, Mariana Novo [UNESP]; Gaeta, Henrique Hessel [UNESP]; Bittencourt Rodrigues, Caroline Fabri [UNESP]; Cruz Costa, Caroline Ramos da [UNESP]; Toyama, Daniela de Oliveira; Domingues Passero, Luiz Felipe [UNESP]; Laurenti, Marcia Dalastra; Toyama, Marcos Hikari [UNESP] (Mdpi Ag, 2017)
Rhamnetin (Rhm), 3-O-methylquercetin (3MQ), and Rhamnazin (Rhz) are methylated derivatives of quercetin commonly found in fruits and vegetables that possess antioxidant and anti-inflammatory properties. Phospholipase A2 (PLA2) displays several important roles during acute inflammation; therefore, this study aimed at investigating new compounds able to inhibit this enzyme, besides evaluating creatine kinase (CK) levels and citotoxicity. Methylated quercetins were compared with quercetin (Q) and were incubated with secretory PLA2 (sPLA2) from Bothrops jararacussu to determine their inhibitory activity. Cytotoxic studies were performed by using the J774 cell lineage incubated with quercertins. In vivo tests were performed with Swiss female mice to evaluate decreasing paw edema potential and compounds' CK levels. Structural modifications on sPLA2 were made with circular dichroism (CD). Despite Q and Rhz showing greater enzymatic inhibitory potential, high CK was observed. Rhm exhibited sPLA2 inhibitory potential, no toxicity and, remarkably, it decreased CK levels. The presence of 3OH on the C-ring of Rhm may contribute to both its anti-inflammatory and enzymatic inhibition of sPLA2, and the methylation of ring A may provide the increase in cell viability and low CK level induced by sPLA2. These results showed that Rhm can be a candidate as a natural compound for the development of new anti-inflammatory drugs.
Keywords: rhamnetin; methylated quercetins; phospholipase A2; anti-inflammatory; Bothrops jararacussu